(untitled) (Journal of Human Sciences, 2024)
This study deals with presentation and analysis of the approach of the Hanbali masters in working with single narrations, and the controls they set for accepting it. This study aims to find out the most important opinions of the scholars of the doctrine on this subject, and to know the conditions they stipulated for adopting single narrations, the extent of its validity according to their scholars, and their method of working with hadith. The mursal, their position on the hadith narration if it violates analogy, and their responses to the conditions of the Hanafi and Maliki masters with which they rejected the hadith narration. This study concluded with jurisprudential applications on the approach of the Hanbali masters in their acceptance of the hadith hadiths.